2005
DOI: 10.1182/blood-2004-06-2180
|View full text |Cite
|
Sign up to set email alerts
|

Membrane receptors are not required to deliver granzyme B during killer cell attack

Abstract: Granzyme B (GzmB), a serine protease of cytotoxic T lymphocytes and natural killer (NK) cells, induces apoptosis by caspase activation after crossing the plasma membrane of target cells. The mechanism of this translocation during killer cell attack, however, is not understood. Killer cells release GzmB and the membrane-disturbing perforin at the contact site after target recognition. Receptor-mediated import of glycosylated GzmB and release from endosomes were suggested, but the role of the cation-independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 39 publications
9
60
0
Order By: Relevance
“…Granzymes likely dissociate from serglycin before they enter target cells (63). Granzymes bind to the target cell membrane by electrostatic interactions (granzymes are very positively charged with pIs ~9-11, and the cell surface is negatively charged) (64)(65)(66) and also by specific receptors, such as the cation-independent mannose-6-phosphate receptor (67). However, specific receptors are not required for binding and cytotoxicity (64,68,69).…”
Section: Granzyme Release Uptake and Trafficking In Target Cellsmentioning
confidence: 99%
“…Granzymes likely dissociate from serglycin before they enter target cells (63). Granzymes bind to the target cell membrane by electrostatic interactions (granzymes are very positively charged with pIs ~9-11, and the cell surface is negatively charged) (64)(65)(66) and also by specific receptors, such as the cation-independent mannose-6-phosphate receptor (67). However, specific receptors are not required for binding and cytotoxicity (64,68,69).…”
Section: Granzyme Release Uptake and Trafficking In Target Cellsmentioning
confidence: 99%
“…Interactions between the positively charged PR3 and PMN membranes cannot simply be due to a charge effect as PR3 binding was not blocked by the highly positively charged gran-zyme B (15) or by high salt concentrations 5 (4). Direct interactions of PR3 to reconstituted lipid bilayers and lipid vesicles were recently studied, and a dissociation constant of 4.5 M relating to lipid vesicles with a mixed composition has been determined.…”
Section: Proteinase 3 (Pr3)mentioning
confidence: 99%
“…Recent work has suggested that the level of HSPGs on target cells may not be associated with susceptibility to GrBinduced apoptosis (40). Nevertheless, the authors of the same study concluded that HSPGs are required for GrB binding and uptake by target cells.…”
Section: Discussionmentioning
confidence: 75%
“…Because xyloside treatment reduces the level of both HS and CS GAG expression, the results suggest that both GAGs participate in a GrB uptake that contributes to cell-mediated cytotoxicity. Kurschus et al relied on enzymatic removal of HS GAGs with heparinase, monitoring depletion with an anti-N-sulfated glucosamine antibody (40). This limited treatment may not have effectively removed GrB-binding GAGs, either HS and/or CS, below a threshold that prevented induction of cell death.…”
Section: Discussionmentioning
confidence: 99%